2008
DOI: 10.1088/0960-1317/18/7/075033
|View full text |Cite
|
Sign up to set email alerts
|

An improved in-plane thermal folded V-beam actuator for optical fibre alignment

Abstract: This paper presents an improved thermal actuator design, providing high work per unit of chip area. The actuator was developed for high accuracy fibre alignment. This application requires that the fibre tip is moved by pushing close to its end, posing geometric design constraints on the actuator design. The basic structure of the actuator is a parallelogram, consisting of a non-moving base, a bar parallel to the base placed orthogonal to the fibre axis in contact with the fibre, and heater arms and reinforced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 12 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…An alternative approach, investigated in this work, is to amplify the motion of the proof mass. The magnification of small displacements using compliant MEMS structures is well known [11] and has been used previously in applications such as strain sensing [12] and thermal [13] and piezoelectric [14] actuation. Recently, structures that amplify the movement of a proof mass in a capacitive accelerometer have also been developed.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach, investigated in this work, is to amplify the motion of the proof mass. The magnification of small displacements using compliant MEMS structures is well known [11] and has been used previously in applications such as strain sensing [12] and thermal [13] and piezoelectric [14] actuation. Recently, structures that amplify the movement of a proof mass in a capacitive accelerometer have also been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Yang,et al,in [4], and the design of optical fiber alignment devices, as reported by W.P. Sassen, et al, in [5]. The feasibility of implementing vertical thermal actuators based on the chevron topology has been confirmed in [6].…”
Section: A Design Considerationsmentioning
confidence: 88%
“…Fig. 3b shows a single-ended or folded V-beam actuator [57,58]. Here, the beam array is divided into sets of cold and hot arms tied by a crossbeam at the free end, and the anchors are subdivided so that a current may be passed only through the hot arms, leaving the cold arms as tethers that constrain longitudinal expansion.…”
Section: Nems Actuator Designsmentioning
confidence: 99%